Cone repair: our experience of anatomical reconstruction of Ebstein’s anomaly - Khanenova, V. A.; RiznykА. S.; MeshkovaМ. S.; Semeniuk, V. P.; BabliakО. D.; RudenkoN. М. (Ukrainian Journal of Cardiovascular Surgery, 2016)
This article summarizes the experience of surgical treatment in patients with Ebstein’s anomaly (Cone repair). Early echocardiography showed significant reduction of tricuspid insufficiency. The follow-up showed clinical improvement in a clinical condition in this patients, low incidence of reoperations, and no need for tricuspid valve replacement. Further studies and longer follow-up are required to evaluate the behavior of the tricuspid valve and right ventricle after this procedure.